(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
Stress, whose roots can be found in many aspects of the profession itself, became a serious disorder of the 20th century and rightfully earned the name “the disease of the new millennium,” while the twentieth century has been called “the century of stress.” The profession, traditionally understood as an activity we perform in order to meet a certain social need by carrying out a specific social function— for which we receive compensation necessary for the livelihood of ourselves and our families—plays an important role in a person’s life. The profession occupies the lives of many of us and significantly affects our well-being.